Total Parenteral Nutrition or Early Enteral Nutrition: Outcome and Economic Impact after Pancreatoduodenectomy (Journal of Surgical Sciences, 2026)
Background: Recent concept of enteral nutrition provision with good outcome gradually changes the current practice of postoperative management. But commercially available enteral formula is often costly, not affordable by native people, and often not tolerable. This study was carried out to compare the effect of total parenteral nutrition (TPN) versus early enteral nutrition (EEN) on postoperative outcomes and nutrition related cost after pancreatoduodenectomy.Methods: Thirty patients who underwent pancreatoduodenectomy within one year in the Department of Hepatobiliary, Pancreatic & Liver Transplant Surgery, BSMMU included and categorized into two groups; EEN(n=15) group: enteral feeding made with indigenous food and TPN (n=15) group: only parenteral nutrition continued up to six/seven post-operative days (POD). In all the patients, biochemical parameter was measured on POD 1, 3, 7 & 14 for assessing primary end point (Nutritional condition, morbidity and mortality) and secondary end point (length of postoperative hospital stays, albumin requirement and nutrition related cost).Results: EEN was shown to have a significant effect on reducing the overall complications rate (3/15 vs 10/15, p